A Comparison of Language Learning Strategies Adopted by Secondary and University Students in Hong Kong - Andrew, Yau-hau Tse (Centre for Promoting Ideas, USA, 2011)

(untitled)
Language learning strategies (LLS) that help learners enhance their language competence have played an important role in language learning; their spectrum has become one fertile area of research in second language acquisition (MacIntyre, 1994). The objective of this study is to investigate the LLS used by secondary and university students and the background variables influencing their use of LLS. An individual background questionnaire and the Language Learning Strategy Inventory (LLSI) were used as the research instruments. The LLSI was modified by the researcher from Oxford’s (1990) Strategy Inventory for Language Learning (SILL). The findings reveal that grades 12-13 students use memory strategies (medium use) and first year university students adopt compensation strategies (medium use) in learning English. To conclude, grades 12-13 students in Hong Kong used LLS in a low to medium use, with no high use; whereas university students used LLS in medium use, with no high use.